Transition Systems with Independence and Multi-Arcs - Hildebrandt, Thomas Troels; Sassone, Vladimiro (BRICS Report Series, 1997)
We extend the model of transition systems with independence in order to provide it with a feature relevant in the noninterleaving analysis of concurrent systems, namely multi-arcs. Moreover, we study the relationships between the category of transition systems with independence and multi-arcs and the category of labeled asynchronous transition systems, extending the results recently obtained by the authors for (simple) transition systems with independence (cf. Proc. CONCUR’96), and yielding a precise characterisation of transition systems with independence and multi-arcs in terms of (event-maximal, diamond-extensional) labelled asynchronous transition systems.